Implementation of Disaster Mitigation Introduction through Digital Video Media for Early Childhood at Kindergarten Melati 03 Menteng, Central Jakarta - Sudewo, Dimas (International Journal of Environmental Communication (ENVICOMM), 2024)
The occurrence of many natural disasters is caused by both natural and non-natural factors, resulting in numerous casualties, environmental damage, financial losses, and psychological impacts. The importance of understanding disaster preparedness should be instilled from an early age, especially in children. This knowledge includes disaster mitigation strategies that encompass steps to reduce risks before, during, and after disasters. Therefore, this research will examine the implementation of visual learning in early childhood, particularly at Kindergarten Melati 03 Menteng, Central Jakarta, concerning disaster mitigation. This study utilizes qualitative methods to provide factual and in-depth descriptions of the research findings. The subjects of this study are 10 kindergarten children and teachers/educators at Kindergarten Melati 03 Menteng, Central Jakarta. The research findings indicate that digital media in the form of videos can be used as a learning resource to introduce flood disaster mitigation to young children. Children gain better understanding of flood disasters and their risk factors after viewing digital video learning media. The development of flood disaster mitigation programs in the form of digital video learning media has been shown to enhance knowledge and foster early disaster responsiveness among young children. The implementation of disaster mitigation programs through video learning offers several benefits, including easy accessibility, user-friendliness, general applicability, and suitability for various settings.